Child and adolescent psychopathology : a casebook - Wilmshurst, Linda (Los Angeles, CA : SAGE Publications, Inc, 2018)
Child and Adolescent Psychopathology: A Casebook provides 25 real-life cases to give students a deeper understanding of a wide range of disorders within the context of the DSM-5. As they explore complex cases, students learn to integrate theory into research-based assessments and interventions. Each case provides opportunities to practice clinical skills in the assessment, diagnosis, and treatment of childhood disorders from a number of theoretical perspectives and at various levels of interest and expertise. Reflecting the latest developments in the field, the Fourth Edition now includes a new case study on social phobia/social anxiety disorder, additional post-case questions, and an expanded introductory chapter discussing trends in case formulation.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Child psychopathology -- Case studies; Adolescent psychopathology -- Case studies